2002
DOI: 10.1126/science.1075078
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Driven Bedrock Incision in an Active Mountain Belt

Abstract: Measurements of fluvial bedrock incision were made with submillimeter precision in the East Central Range of Taiwan, where long-term exhumation rates and precipitation-driven river discharge are independently known. They indicate that valley lowering is driven by relatively frequent flows of moderate intensity, abrasion by suspended sediment is an important fluvial wear process, and channel bed geometry and the presence of widely spaced planes of weakness in the rock mass influence erosion rate and style.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
241
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(255 citation statements)
references
References 17 publications
(21 reference statements)
14
241
0
Order By: Relevance
“…Floods efficiently erode and transport sediment stored in the riverbed (Baker and Kale, 1998;Bookhagen et al, 2005;Coppus and Imeson, 2002;Hartshorn et al, 2002). On 26 June 2005, a flood occurred in the Parechu River, a main tributary of the Spiti River, which was caused by the failure of a landslide dam that blocked the river (cf.…”
Section: The 26 June 2005: Parechu Floodmentioning
confidence: 99%
“…Floods efficiently erode and transport sediment stored in the riverbed (Baker and Kale, 1998;Bookhagen et al, 2005;Coppus and Imeson, 2002;Hartshorn et al, 2002). On 26 June 2005, a flood occurred in the Parechu River, a main tributary of the Spiti River, which was caused by the failure of a landslide dam that blocked the river (cf.…”
Section: The 26 June 2005: Parechu Floodmentioning
confidence: 99%
“…For example, Hartshorn et al [2002] argued that valley lowering is driven by frequent, moderate intensity floods which mobilize the coarse bed load and abrade underlying bedrock while D'Arcy and Whittaker [2014] found that channel steepness is significantly suppressed by higher precipitation due to a concomitant increase in stream power. Hillslopes are then expected to passively follow decreased or increased rates of base-level lowering by either (a) steepening or lowering hillslope angle: in transport-limited (soil mantled) conditions, the rate of soil creep/mass movement will slowly change due to a change in base level and increased/decreased soil diffusivity [Fernandes and Dietrich, 1997]; or (b) in high-relief terrain maintain roughly linear (threshold) hillslopes but increase/decrease the rate of landsliding [Burbank et al, 1996;Tucker and Bras, 1998;Tucker and Hancock, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, by controlling the sediment supply to adjacent channels, hillslope processes directly influence channel dynamics, i.e., hillslope processes may respond to changing precipitation by either increasing or decreasing the sediment supply to adjacent channels which either enhances or impedes fluvial wear of the channel. Thus, both hillslopes and channels respond independently and interdependently [Brunsden and Thornes, 1979;Brunsden, 1993;Sklar and Dietrich, 1998;Hartshorn et al, 2002;Dietrich et al, 2003;Turowski et al, 2013;Finnegan et al, 2014;Michaelides and Singer, 2014] to changing precipitation and it is far from clear which leads the response or whether indeed their coupling means that they respond simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, erosion could occur directly due to the stresses exerted by the fluid on the rock. Although all of the processes in these four groups occur in different locations and at different times, and may interact to produce the erosional result, corrasion is probably the dominant mechanism in high-energy natural environments such as many mountain rivers (Hancock et al, 1998;Hartshorn, Hovius, Dade, & Slingerland, 2002;Wilson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%